Development of a Platinum Complex as an anti‐Amyloid Agent for the Therapy of Alzheimer's Disease. Issue 12 (10th February 2013) - Kenche, Vijaya B.; Hung, Lin W.; Perez, Keyla; Volitakes, Irene; Ciccotosto, Guiseppe; Kwok, Jeffrey; Critch, Nicole; Sherratt, Nikki; Cortes, Mikhalina; Lal, Varsha; Masters, Colin L.; Murakami, Kazuma; et al.
<x xml:space="preserve">Abstract</x> Brainwash! A platinum complex (see scheme) was developed that could be administered orally and reduce the amyloid burden in the brains of transgenic mouse models suffering from Alzheimer's disease. Analyses of brain tissues showed that treatment with the Pt compound led to a 26 % decrease in the number of amyloid β‐peptide plaques.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>